2003
DOI: 10.1191/0961203303lu337oa
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of danazol corticosteroids and cytotoxic drugs in the treatment of hematologic manifestations of systemic lupus erythematosus

Abstract: The purpose of this study was to compare the long-term effectiveness among danazol, corticosteroids, cytotoxics, and dapsone in the treatment of hematological manifestations of systemic lupus erythematosus (SLE). Medical charts of all patients seen at the Rheumatic Disease Unit from January to December of 1998 were reviewed. Patient characteristics, disease and treatment information were collected. The main outcome measures were the cause of and time to discontinuation of drugs used to treat hematological mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…Nos casos refratários à corticoterapia, ou por ocasião da necessidade de altas doses de manutenção, pode-se associar imunossupressores (48) (D), (49) (D), como a azatioprina (48) (D), o micofenolato de mofetil (50) (D), a ciclosporina (51) (D) ou o danazol (46) (D), (49) (D), (52) (D). Pode ser indicada também administração de anti-CD20, sobretudo nos casos de risco maior (53) (D).…”
Section: Comprometimento Hematológicounclassified
“…Nos casos refratários à corticoterapia, ou por ocasião da necessidade de altas doses de manutenção, pode-se associar imunossupressores (48) (D), (49) (D), como a azatioprina (48) (D), o micofenolato de mofetil (50) (D), a ciclosporina (51) (D) ou o danazol (46) (D), (49) (D), (52) (D). Pode ser indicada também administração de anti-CD20, sobretudo nos casos de risco maior (53) (D).…”
Section: Comprometimento Hematológicounclassified
“…Uncontrolled studies and case series have reported successful result with AZA, CYA, IVIG, danazol and, as a last therapeutic option, splenectomy. [68][69][70] Only five SLE patients with HA treated with MMF have been reported. Two cases were described by Alba et al 71 In both cases HA was associated with lupus GLN and recovered completely after treatment with MMF (2 g/day).…”
Section: Haematological Abnormalitiesmentioning
confidence: 99%
“…The overall clinical picture can determine drug selection, just as a more active disease can command cytotoxic therapy [101,102]. There is no evidence of one treatment being superior to the other [103].…”
Section: Limitationsmentioning
confidence: 99%